Following the money : the Enron failure and the state of corporate disclosure - Benston, George J. (AEI-Brookings Joint Center for Regulatory Studies, 2003)
"A few years ago, Americans held out their systems of corporate governance and financial disclosure as models to be emulated by the rest of the world. But in late 2001 U.S. policymakers and corporate leaders found themselves facing the largest corporate accounting scandals in American history. The spectacular collapses of Enron and WorldCom - as well as the discovery of accounting irregularities at other large U.S. companies - seemed to call into question the efficacy of the entire system of corporate governance in the United States." "In response, Congress quickly enacted a comprehensive package of reform measures in what has come to be known as the Sarbanes-Oxley Act. The New York Stock Exchange and the NASDAQ followed by making fundamental changes to their listing requirements. The private sector acted as well. Accounting firms - watching in horror as one of their largest, Arthur Andersen, collapsed after a criminal conviction for document shredding - tightened their auditing procedures. Stock analysis and ratings agencies, hit hard by a series of disclosures about their failings, changed their practices as well." "Using the Enron case as a point of departure, the authors argue that the major problem lies not in the accounting and auditing standards themselves, but in the system of enforcing those standards. Rather than attempting to craft a single set of accounting and reporting standards for all companies throughout the world, the authors advise policymakers to allow competition between the two major sets of standards: Generally Accepted Accounting Principles and International Financial Reporting Standards."--Jacket